2016
DOI: 10.1016/j.ijrobp.2016.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Geographic Disparity in the Use of Hypofractionated Radiation Therapy Among Elderly Women Undergoing Breast Conservation for Invasive Breast Cancer

Abstract: PURPOSE Research demonstrates that the use of short-course (hypofractionated) radiotherapy (RT) breast cancer in the US has lagged behind other countries, despite evidence from randomized trials. This study evaluates geographic heterogeneity in the delivery of hypofractionated radiotherapy among Medicare beneficiaries across the US. METHODS We identified 190,193 patients from the Centers for Medicare and Medicaid Services (CMS) Chronic Conditions Warehouse. The study included patients over age 65 diagnosed w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 34 publications
1
23
0
Order By: Relevance
“…Clinical management factors and financial issues also influence the inconsistent use of HFRT implementation. Healthcare environment, the strength of HFRT recommendations in institutional protocols, implementation of the clinical pathway or active advocacy for the shorter fractionation schedules, access to peer review, continuing medical education and existence of BC-dedicated ROs were all demonstrated as important factors in implementing new evidence-based recommendations [30,[46][47][48]. Similar patterns were reflected in our survey, as HF-WBI was more often preferred by ROs who worked in academic environments and dedicated !50% of their clinical time to patients with BC, thus demonstrating the importance of working context and professional experience.…”
Section: Discussionsupporting
confidence: 72%
“…Clinical management factors and financial issues also influence the inconsistent use of HFRT implementation. Healthcare environment, the strength of HFRT recommendations in institutional protocols, implementation of the clinical pathway or active advocacy for the shorter fractionation schedules, access to peer review, continuing medical education and existence of BC-dedicated ROs were all demonstrated as important factors in implementing new evidence-based recommendations [30,[46][47][48]. Similar patterns were reflected in our survey, as HF-WBI was more often preferred by ROs who worked in academic environments and dedicated !50% of their clinical time to patients with BC, thus demonstrating the importance of working context and professional experience.…”
Section: Discussionsupporting
confidence: 72%
“…Owing to wide variations in the patterns of care surrounding fractionation (7,8), multiple randomized trials directly comparing hypofractionation with standard radiation were initiated, with recent long-term results confirming equivalence (9-13). However, despite the development of clinical guidelines by the American Society for Radiation Oncology in 2011 (14) followed by the American Board of Internal Medicine's Choosing Wisely campaign in 2013 (7), the uptake of hypofractionation in the United States has been slow (15,16), with evidence that practice patterns vary widely based on geography (15,17).…”
Section: Introductionmentioning
confidence: 99%
“…Limited practice-related factors have also been investigated, with treatment in a hospital-based clinic and higher density of radiation oncologists increasing the likelihood of receiving hypofractionation (16,17), whereas overall population density had no impact (15). The impact of providerspecific data, however, is limited to data from a single-state multi-institution study (21).…”
Section: Introductionmentioning
confidence: 99%
“…Lower paces of neighborhood repeat, and restricted radiation-actuated horribleness have been accounted for approaches [12]. Schedules utilized in these investigations went from 40 to 44 Gy given in 15 to 16 portions over a 21 days' time frame, with everyday parts of 2.5 to 2.7 Gy [13], [14].…”
Section: Introductionmentioning
confidence: 99%